Public Health as a Matter of Concern: Victorian England, 1834-1848. (May 2019) - Strand, Michael
Public health is currently evolving, expanding, and reinforcing itself as a governance project in which health authorities' concerns meet and blend with epidemiology and civil engineering. Rarely, however, are those concerns found worthy of examination, at least not to account for the multiplying involvements of public health, its ability to find political life in things, and its many translations. The shape of public health is dictated as much by its matters of concern as it is by biopolitical and brute matters of fact. This article presents a genealogy of public health in Victorian England between 1834 and 1848 in order to glimpse the matters of concern around which it stabilized. The political medicine that preceded public health holds the clue in its assertion of life as a form of worth, as prominent a criterion for the assessment of sociomaterial arrangements as profitability or efficiency. This article describes public health as an ensemble presence, a unique gathering, in which political will follows medical diagnosis, and life is worth at least as much as money.